The substantive rationality of self-management practices: an analysis of the organizational dynamics of women in solidarity economy from the perspective of oral history - Soares, Maria de Nazaré Moraes; Rebouças, Silvia Maria Dias Pedro; Lazaro, Jose Carlos (Revista de Administração da UFSM, 2020)
Purpose – The research aims to discuss substantive rationality in the context of Solidarity Economy (SE) and women’s self-management practices in the Solidarity and Feminist Economy Network [SFEN], based on the voices of women themselves. Design/methodology/approach – The research uses an exploratory and qualitative, from the perspective of thematic oral history. It is a search for representativeness of other forms of organization through otherness and a post-colonial view of the Administration. Findings - The productive groups of women of the SFEN are configured as substantive organizations. Under the self-management paradigm, reveal an alternative way of producing and commercialization, bringing together the dimensions of work and life in order to allow the construction of an inclusive economy, which could be alignment with the enclave “isonomy” of Guerreiro Ramos. Research limitations/implications – As an exploratory study, it was not possible in this article go deepen the gender issue in the daily practice of women in the productive group. Practical implications – The use of the self-management paradigm in an inclusive economy situation presents these production groups with a real alternative to understanding themselves as active participants in the economy. Social implications - The study brings the reflection of the participants of the productive groups about their active position in society, generates a self-assessment of their activities, serving the analysis also as an opening for reassessments and reapplications of the self-knowledge process of such groups. Originality/value – There is a gap in management research discussing solidarity economy, self-management, feminist organizations and substantive organizations by Guerreiro Ramos.